Policy Implementation of Electric Vehicle (EV) Promotion - Bunnag, Jessataporn; Kalyanamitra, Kamolporn; Niyomyaht, Satit; Lakkanapichonchat, Tassanee (Journal of Graduate MCU KhonKaen Campus, 2023)
This research aimed (1) to study the state of policy implementation of electric vehicle (EV) promotion, (2) to study the problems and obstacles in the policy implementation of electric vehicle (EV) promotion, and (3) to study the recommendations for improving the policy implementation of electric vehicle (EV) promotion. The research was qualitative. Key informants in the study were 25 people who participated in the implementation of the policy to promote the use of electric vehicles (EV) by a purposive selection. The research tool was an interview form. The data were analyzed by adescriptive summary. The results found that 1) the state of policy implementation of electric vehicle (EV) promotion were characterized and the objectives of the policy were comprehensive, clear, well supported by the authority/leader, ongoing budget support. The organization implemented the policy operators in accordance with the policy. Personnel, who implemented the policy were knowledgeable, competent, and had a positive attitude towards the policy. Organizations had coordinated and collaborated to push forward the policy, social, economic and political conditions led to increased awareness of the use of electric vehicles. 2) the problems and obstacles in the policy implementation of electric vehicle (EV) promotion was inappropriate laws, limited budget, inadequate personnel, some labor and industry sectors had been affected, investor uncertainty, lack of advanced technology and raw materials, high price of electric cars, people’s attitudes, 3) the suggestions for improving the policy implementation of electric vehicle (EV) promotion. There must be a policy to create supply and demand, developed technology and skilled workers, created the right environment, public relations to strengthen speeding up regulations and obstructive laws.